The aquaculture supply chain in the time of covid-19 pandemic: Vulnerability, resilience, solutions and priorities at the global scale. Issue 127 (January 2022) - Mangano, M.C.; Berlino, M.; Corbari, L.; Milisenda, G.; Lucchese, M.; Terzo, S.; Bosch-Belmar, M.; Azaza, M.S.; Babarro, J.M.F.; Bakiu, R.; Broitman, B.R.; Buschmann, A.H.; et al.
Abstract: The COVID-19 global pandemic has had severe, unpredictable and synchronous impacts on all levels of perishable food supply chains (PFSC), across multiple sectors and spatial scales. Aquaculture plays a vital and rapidly expanding role in food security, in some cases overtaking wild caught fisheries in the production of high-quality animal protein in this PFSC. We performed a rapid global assessment to evaluate the effects of the COVID-19 pandemic and related emerging control measures on the aquaculture supply chain. Socio-economic effects of the pandemic were analysed by surveying the perceptions of stakeholders, who were asked to describe potential supply-side disruption, vulnerabilities and resilience patterns along the production pipeline with four main supply chain components: a) hatchery, b) production/processing, c) distribution/logistics and d) market. We also assessed different farming strategies, comparing land- vs. sea-based systems; extensive vs. intensive methods; and with and without integrated multi-trophic aquaculture, IMTA. In addition to evaluating levels and sources of economic distress, interviewees were asked to identify mitigation solutions adopted at local / internal ( i.e., farm-site) scales, and to express their preference on national / external scale mitigation measures among a set of a priori options. Survey responses identified the potential causes of disruption, ripple effects, sources of food insecurity, and socio-economic conflicts. They also pointed to various levels of mitigation strategies. The collated evidence represents a first baseline useful to address future disaster-driven responses, to reinforce the resilience of the sector and to facilitate the design reconstruction plans and mitigation measures, such as financial aid strategies. Highlights: Rapid global assessment of COVID-19 control measures effects. Stakeholders perceptions survey on socio-economic effects of the pandemic. Aquaculture supply chain: hatchery, production/processing, distribution, marketing. Supply-side disruption, vulnerabilities and resilience patterns were highlighted. Adopted and preferred mitigation solutions at internal and external scale.